Experimental analysis of combined utilization of CuO nanoparticles in latent heat storage unit and absorber coating in a single-slope solar desalination system - Selimefendigil, Fatih; Sirin, Ceylin; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2022)
In this survey, impact of combined utilization of copper oxide (CuO) nanoparticles both in thermal energy storage unit and absorber coating (matt black paint) on the performance of a single-slope solar still has been investigated experimentally. In this context, four different solar desalination systems including a conventional solar still, solar still with thermal energy storage unit, solar still with CuO nano-embedded latent heat storage unit and solar still with CuO nano-enhanced absorber coating and thermal energy storage unit have been developed, fabricated and empirically analyzed. Experimental results showed that combined employing nanoparticles upgraded accumulated productivity as 26.77% in comparison to conventional solar still. Also, energy and exergy efficiency values were enhanced from 15.96% to 19.90% and from 1.25% and 2.01%, respectively with the use of combined modification.
Keywords: Solar still; CuO nanoparticles; Thermal energy storage; Black paint; Modeling